Evaluación de impactos de la deforestación sobre la entomofauna de la cordillera occidental, interésespecífico, las abejas sin aguijón tribu meliponini, en el sector solonso. La Mana. Cotopaxi. 2023. - Panchi Panchi, Cristian Fabian (2023)
This project was carried out in the Yanayacu parish, La Mana canton, in the Solonso sector between an altitude of 480 and 600 meters above sea level. Having as objectives: Identify the species of stingless bees Meliponini tribe present in the Solonso sector; Determine the number of existing stingless bees by species in the sector.In order to determine the presence of stingless bees, four types of trapping were carried out:Harris, Platos, Malaise and entomological network. To recognize the species, dichotomous keys were used at the National Institute of Biodiversity (INABIO). Obtaining four species of stingless bees: Scaptotrigona with a total of 100 individuals, Flavolineata Friese with a total of 36 individuals, M. seminigra with a total of 48 individuals and Plebeia sp with a total of 51 individuals. Stingless bee nests belonging to the two identified species were also found at different heights in the Solonso sector. The abundance of bees is due to meteorological factors because the precipitation is low from the month of August (25.4 mm), September (21.3 mm) given that the largest collection of samples of this research project was carried out in these months. . The highest rainfall (615.9 mm) occurs in the sector in the month of February.Therefore, the presence of the melipona species is very scarce.